Phenolic content, antioxidant and antiproliferative activities of six varieties of white sesame seeds (Sesamum indicum L.). Issue 10 (17th January 2017) - Lin, Xiaohui; Zhou, Lin; Li, Tong; Brennan, Charles; Fu, Xiong; Liu, Rui Hai
Abstract : This article investigates the total phenolics, antioxidant and antiproliferative activities of six varieties of white sesame seed. Abstract : Little work has been conducted on the evaluation of antioxidant and antiproliferative activities of different sesame seed varieties. This article compared the total phenolics, antioxidant contents, and the antiproliferative activities of six varieties of white sesame seeds. Total contents of phenolics and flavonoids ranged between 370.5–786.8 mg GAE/100 g, DW and 714.0–1354.7 mg CE/100 g, DW, respectively. Antioxidant activity was determined by oxygen radical absorbance capacity (ORAC), hydrogen peroxyl radical scavenging capacity (PSC) and cellular antioxidant activity (CAA) assays. According to the ORAC and PSC assays, the white sesame seeds showed high antioxidant values of 33.94 μmol Trolox equiv./g, DW and 9.39 μmol Vit. C equiv./g, DW, respectively. The free CAA values ranged from 55.66 to 224.45 μmol QE/100 g, DW in the no PBS wash protocol, and 21.88–57.36 μmol QE/100 g, DW in the PBS wash protocol. The proliferation of HepG2 human liver cancer cells were inhibited significantly after exposure to the white sesame seed extracts, with EC50 of antiproliferative activities ranging from 102.54 to 43.92 mg mL −1 . Free phenolics make a major contribution to total phenolic content, antioxidant and antiproliferative activities. This study suggested that white sesame seeds are potential sources of functional food to prevent chronic diseases.